2013
DOI: 10.1016/j.chemosphere.2013.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Development of permeable reactive biobarrier for the removal of PAHs by Trichoderma longibrachiatum

Abstract: In this work, the formation of permeable reactive biobarriers (PRBBs) using Trichoderma longibrachiatum over nylon sponge as bioreactive medium for removal of polycyclic aromatic hydrocarbons (PAHs) was studied. Colony formation was pretested without PAH presence by inoculation of fungus into nylon sponge. The fungus formed a large quantity of strongly adhesive biofilm among nylon sponge. Afterwards, the ability of the developed bioreactive medium was tested to remediate phenanthrene in aqueous medium and in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Polycyclic aromatic hydrocarbons (PAHs) with two or more fused aromatic rings are a class of ubiquitous pollutants and are formed in the process of incomplete combustion of fossil fuel, waste incineration and industrial production (Chang et al, 2002;Chen et al, 2013;Cobas et al, 2013). Moreover, the hydrophobicity and structural stability of PAHs improve with an increase of the fused aromatic rings.…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) with two or more fused aromatic rings are a class of ubiquitous pollutants and are formed in the process of incomplete combustion of fossil fuel, waste incineration and industrial production (Chang et al, 2002;Chen et al, 2013;Cobas et al, 2013). Moreover, the hydrophobicity and structural stability of PAHs improve with an increase of the fused aromatic rings.…”
Section: Introductionmentioning
confidence: 99%
“…PY2 effectively removed pyrene up to 96.0 % and volatilized arsenic up to 84.1 %, while bioremediation ability was 87.2 % in contaminated soil with 100 mg/kg pyrene [131]. Another unique and innovative approach for removal of PAHs was adopted by Cobas et al [132] who demonstrated 90 % removal of phenanthrene in 14 days by developing permeable novel reactive biobarriers of Trichoderma longibrachiatum on nylon sponge. Fungal biocatalysis is being used in the whole cell systems for the textile wastewater treatment [133].…”
Section: Technological Advances In Fungal Bioremediationmentioning
confidence: 99%
“…The column packing consisted of seven layers of nylon sponge (4.3 cm diameter) interspersed with 6 agar layers (11 ± 0.1 g of AG containing 9.9 mg of immobilized P. stutzeri ). The packed bed reactor worked with minimal medium described by Cobas et al using 100 µmol L ‐1 of PHE as the sole carbon and energy source. The temperature was kept at 30 °C by the circulation of temperature‐controlled water, and constant aeration of 20 mL min ‐1 was given.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of PRBBs implies that a bioreactive medium is placed in the subsurface across the flow of a plume of contaminated groundwater, which must move through the medium as it flows, typically under a natural gradient, thereby creating a passive treatment system . This environmentally friendly technology utilizes naturally occurring microorganisms, mainly bacteria and/or fungi, as bioreactive medium for the degradation of pollutants in the groundwater . The microorganism metabolism induces the breakdown of organic compounds through mineralization into inorganic minerals, H 2 O, CO 2 (aerobic) or CH 4 (anaerobic).…”
Section: Introductionmentioning
confidence: 99%